PENERAPAN MEDIA PEMBELAJARAN BERBASIS GENIALLY DALAMPEMBELAJARAN IPAS UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V UPTD SD NEGERI 1 BONIPOI KOTA KUPANG - Baoknenok, Mira Y. P; Koro, Maxsel; Devi, Rista A. (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research was conducted at UPTD SD Negeri 1 Bonipoi Kupang City, with 20 subjects, 8 male students and 12 female students. In this research, the techniques used were observation and test techniques. Based on the results of the initial data test, the results of the study showed that in cycle 1 out of 20 students, 12 students completed (60%) because students prepared themselves to learn well, listened to the teacher's explanation regarding the material on hearing because of sound well, sat quietly responding to directions from the teacher, asked about material that was not yet understood. The other 8 students (40%) had not reached the completion standard because students did not pay enough attention to the teacher's delivery of topics, students were not orderly and students were less active in learning. Furthermore, in cycle 2, student learning outcomes increased from 20 students, 18 students completed (90%) because students prepared themselves to study well, students were able to work on LKPD from the teacher, students were able to work together in groups, students sat quietly and listened to directions from the teacher, while 2 other students had not completed (10%) because students did not pay enough attention to questions from the teacher, students were not focused on following the learning, students still did not understand the learning material. Based on the research results above, it is concluded that in the application of genially-based learning media in science learning, the listening material is because of the sound on student learning outcomes and is in accordance with the minimum completion criteria expected by researchers